IMPLEMENTASI MORAL TRIANGLE LICKONA DALAM MEMBENTUK KARAKTER YANG BAIK DAN KARAKTER AKHLAK KENABIAN MUHAMMAD SAW BAGI SISWA - Moh. Soheh; Ummu Kulsum (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2021)
Thomas Lickona, has a moral triangle in shaping good character, including moral knowledge, moral feelings and moral actions. The moral triangle is interconnected with one another, so that in its implementation it is able to shape the character of students better, if guidance is carried out continuously by the teacher. Besides that, the dynamics of the prophetic nature of Muhammad SAW, are able to be role models for students. Because by having 4 moral characters possessed by Rasulullah, As-Siddiq, Al-Amanah, At-Tabligh and Al-Fatanah, students can have good morals. The combination of the two can shape students into modest and responsible individuals and are increasingly aware of their role as students in facing their future. This can be realized if teachers and parents support each other and monitor everything students do either at school or at home. What is more important than this, students with self-awareness want to make changes in themselves by imitating the person of the Prophet Muhammad as a role model for the ummah.